(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This paper examines the use of Computational Fluid Dynamics (CFD) simulations to improve thermal comfort in enclosed spaces, such as theatres, halls, and offices. Thermal comfort is crucial for occupant well-being and productivity, and is influenced by various factors, including air temperature, humidity, and airflow. To create tailored models for specific spaces, we suggest using CFD simulations to predict airflow patterns and temperature distribution, thereby identifying discomfort zones. This research aims to optimize thermal comfort and improve building design and energy efficiency by iteratively adjusting ventilation strategies. The practical applications of this approach include improved design and construction, as well as retrofitting existing buildings. To achieve this, CFD simulations should be integrated into the design phase to proactively address thermal comfort issues and achieve energy-efficient layouts. Customising CFD models for existing buildings allows for the analysis of airflow patterns and optimisation of ventilation strategies to enhance thermal comfort. HVAC systems can be evaluated using CFD to identify areas for improvement and select energy-efficient solutions, leading to enhanced energy efficiency. The benefits of these improvements include enhanced well-being and productivity, as improved thermal comfort can lead to better occupant health and focus, ultimately boosting productivity. Additionally, the risks of Sick Building Syndrome (SBS) can be reduced. CFD analysis can help reduce the risks of Sick Building Syndrome by optimizing ventilation and improving indoor air quality. In the future, it is recommended to integrate CFD simulations with Building Information Modelling for comprehensive thermal comfort analysis. This study highlights the potential of CFD to optimize thermal comfort in enclosed spaces by promoting occupant well-being and energy efficiency through iterative ventilation adjustments. It is important to adhere to established standards when integrating CFD.